2014
DOI: 10.1097/bot.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long Cephalomedullary Nails for the Treatment of Intertrochanteric Hip Fractures in Patients Older than 65 Years

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 19 publications
8
90
0
Order By: Relevance
“…This finding is in contrast to the findings of Hou et al and Boone et al (14,19) Several authors attributed the increase in surgical time and estimated blood loss among patients who had insertions of long cephalomedullary nails to additional reaming of the femoral canal and the insertion of the distal interlocking screw. (4,14,20) We are in agreement with these postulations, especially in a setting where the use of short nails allows the additional benefit of an accompanying jig on which to place the distal interlocking screw, making the procedure easier and faster. The differences between our study and other studies that we observed could be due to our relatively smaller study population and inherent heterogeneity in the surgeons' individual implantation techniques.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This finding is in contrast to the findings of Hou et al and Boone et al (14,19) Several authors attributed the increase in surgical time and estimated blood loss among patients who had insertions of long cephalomedullary nails to additional reaming of the femoral canal and the insertion of the distal interlocking screw. (4,14,20) We are in agreement with these postulations, especially in a setting where the use of short nails allows the additional benefit of an accompanying jig on which to place the distal interlocking screw, making the procedure easier and faster. The differences between our study and other studies that we observed could be due to our relatively smaller study population and inherent heterogeneity in the surgeons' individual implantation techniques.…”
Section: Discussionsupporting
confidence: 72%
“…(4,5,(10)(11)(12)(13)20) Several studies have reported no significant difference in outcome with the use of long or short intramedullary nails to treat simple and multifragmentary pertrochanteric fractures; however, those studies did not consider the presence of osteoporosis in their analysis. (14,19) Hence, the aim of the present study was to review the complications and functional In recent years, there has been growing concern regarding the high risk of implant cut-out in the management of osteoporotic pertrochanteric fractures, as was aptly described by Konstantinidis et al in their cadaveric study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations